KUALIFIKASI OOGMERK PADA PENERAPAN PASAL 362 KUHP - Sandi Rakhmat Wicaksono (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT A fact of life in the development of human history no one is able to live alone apart from other groups of humans, except in forced circumstances and even then its nature is only for a while. It is natural for humans to be social beings who cannot live independently. It means that in human life, they are very dependent on other human beings, namely the desire to live in groups, gather, and be side-by-side and hold relations between each other in society.The method used in this study is a normative juridical method, data or information obtained through library research. From the results of the literature research, secondary data were obtained which included primary legal materials, secondary legal materials and tertiary legal materials. The problem that the author discussed in this thesis is the Oogmerk qualification on the application of Article 362 of the Criminal Code and criminal sanctions for applying Article 362 of the Criminal Code.Based on the results of the study it can be concluded It is stated in Article 362 of the Criminal Code that theft has several elements, namely Objective elements and subjective elements, and Law enforcement (criminal) when viewed from a policy process. formulation, application stage, execution phase. Keywords: Oogmerk, criminal sanctions, theft